Mineral contents of chickpea cultivars (Cicer arietinum L.) grown at different locations of Turkey - Kose, Özge Doganay Erbas; Mut, Zeki (Penerbit Universiti Kebangsaan Malaysia, 2020)
Mineral deficiency-induced diseases and health problems influence billions of people worldwide. Development of edible legumes with high mineral contents will provide significant contributions in reducing the frequency of such diseases. Among the edible legumes, chickpea has quite high nutritional values and quite low production costs, thus commonly grown and consumed worldwide. This study was conducted to determine mineral (potassium, phosphorus, sulphur, calcium, magnesium, sodium, zinc, iron, boron, manganese, copper) contents of eight different chickpea cultivars (Akçin-91, Azkan, Hisar, Akça, Gökçe, Yaşa-05, Işık-05 and Çakır) grown in two different locations (Afyonkarahisar and Yozgat provinces of Turkey) for two years (2015 and 2016). Experiments were conducted in randomized blocks design with three replications. Among the minerals, potassium was highest (6435.2-8231.7 mg kg-) followed by phosphorus (2573.9-3094.0 mg kg-1) and sulphur (1710.9-2060.7 mg kg-1). Among the minerals, copper was lowest followed by boron and manganese. Considering the average of locations, it was observed that Gökçe, Akçin-91, Azkan and Hisar cultivars were prominent with sulphur content; Akça with boron, sodium and calcium contents; Yaşa-05 and Işık-05 with potassium, phosphorus, magnesium, zinc, iron, magnesium, manganese and copper contents. Çakır cultivar was stable for all minerals. The concentrations of seed P, S, Ca, Mg, B and Mn were significantly affected by locations.